Is conservation triage just smart decision making? - Bottrill, Madeleine C.; Joseph, Liana N.; Carwardine, Josie; Bode, Michael; Cook, Carly; Game, Edward T.; Grantham, Hedley; Kark, Salit; Linke, Simon; McDonald-Madden, Eve; Pressey, Robert L.; Walker, Susan; et al. (Trends in ecology & evolution (Amsterdam), 2008)
Conservation efforts and emergency medicine face comparable problems: how to use scarce resources wisely to conserve valuable assets. In both fields, the process of prioritising actions is known as triage. Although often used implicitly by conservation managers, scientists and policymakers, triage has been misinterpreted as the process of simply deciding which assets (e.g. species, habitats) will not receive investment. As a consequence, triage is sometimes associated with a defeatist conservation ethic. However, triage is no more than the efficient allocation of conservation resources and we risk wasting scarce resources if we do not follow its basic principles.